An Analysis Of Educatioanal Value In The Movie AGAK LAEN 2024 - Michael Samuel July Parningotan Sihombing; Merry Rullyanti; Eli Diana (Jurnal Penelitian Multidisiplin Bangsa, 2026)
This research entitled “An Analysis of Educational Value in the Movie Agak Laen (2024)” aims to investigate the educational values contained in the movie and to describe how the main characters manage these values. The study applies a descriptive qualitative method with the primary data taken from the movie itself and supported by secondary data such as journals and articles. The analysis is based on Character Education Theory (Lickona, 1991), Multicultural Education Theory (Banks, 2017), and Social Learning Theory (Bandura, 1997). The findings reveal that the movie conveys various educational values including honesty, responsibility, respect, empathy, tolerance, social solidarity, conflict management, and cooperation. These values are reflected through the characters’ actions, dialogues, and interactions in facing challenges and conflicts. The analysis shows that Agak Laen not only functions as entertainment, but also as a medium that conveys important moral messages to the audience. The characters’ solidarity and tolerance represent multicultural values, while their cooperation and persistence reflect character education and social learning. In conclusion, the movie successfully integrates humor and horror to deliver meaningful educational values, making it an effective medium to teach character, multicultural awareness, and positive social behavior in an entertaining and accessible way.